Yankasa Ram: Body weight, withers hights, scrotal and penis size and sperm reserves - Dauda, C.S. (1984)
Sperm production of the Yankasa ram was investigated to determine the gonadal and extra-gonadal sperm reserves. Biometric measurements and sperm reserve evaluation were made on 7 Yankasa rams aged between 2 to 3 years. The mean body weight of the rams was 30.0 ± 3.1 kg; height at withers 70.0 ± 3.6 cm; and scrotal circumference was 25.6 ± 4.2 cm. The mean weights of testes, epididymides, ductuli diferentia, ampullea and the seminal vesicles were: 193.3 ± 29.4 g; 30.4 ± 3.4 g; 3.7 ± 1.4 g; 2.8 ± 0.5 g and 4.7 ± 0.8 g, respectively. Mean testicular weight was not significantly different between the left and right testes (P